Management of Resistance to Targeted Therapy in EGFR Mutational Lung Adenocarcinoma: A Case Report - Armiza; Sabrina Ermayanti; Afriani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Advances in diagnosis and treatment have enabled a targeted therapy approach to inhibit tumor progression and provide a favorable prognosis. One of the targeted therapies in non-small cell lung cancer (NSCLC) is tyrosine kinase inhibitor (TKI) in mutations epidermal growth factor receptor (EGFR). This study aimed to present a case with the management of resistance to targeted therapy in EGFR-mutated lung adenocarcinoma. Data shows median progression-free survival patients on TKI therapy at 10 to 14 months. Progressive caused by resistance to TKI and assessed using response evaluation criteria in solid tumors (RECIST) 1.1. and confirmed by repeat biopsy. Reported a male patient aged 66 years with adenocarcinoma of the right lung EGFR deletion exon 19 mutation and received afatinib therapy for 16 months. Patients experience oligo progressive in the 13th month of therapy and systemic progression 16th month.